Comparative Assessment of the Communication Strategies Used by the Teachers in Oral Communication in Context in a Private Higher Education Institution in Quezon City - John Timothy Picoy; Crisanto Daing (EduLine: Journal of Education and Learning Innovation, 2024)
The study identified the communication strategies (CS’s) used by the teachers in expressing themselves in English in teaching Oral Communication in Context, compared the assessments of the student-respondents and teacher-respondents, and tested if there were significant relationships among the interplaying variables. It was found out that student-respondents identified asking for clarification as Always used and message abandonment as Rarely used by the teachers. The teacher-respondents identified asking for clarification and asking for repetition as Always used and message abandonment as Rarely used by them. A Mann-Whitney U test examined the significant difference in the assessment of oral communication strategies used by teachers in expressing themselves in English while teaching the identified SHS course when student-respondents are grouped according to gender. The analysis revealed that variables such as paralinguistic devices, literal translation, code switching appeal for help, use of fillers, asking for clarification, and asking for repetition, yielded statistically significant results at .05. Kruskal-Wallis H test was done to examine if there was a significant difference in the scores in terms of oral communication strategies used by teachers in expressing themselves in English when student-respondents are grouped according to academic strand. Few identified variables such as circumlocution, message abandonment, topic avoidance , and asking for clarification, yielded statistically significant results at .05. It is recommended that teachers use only the identified most useful CS’s and avoid those that are useless.